THU0157 'SWITCH ME IF YOU CAN' – REAL LIFE EXPERIENCE OF SWITCHING TO BIOSIMILAR DRUGS FROM GARTNAVEL GENERAL HOSPITAL, GLASGOW, UK. (13th June 2020) - Abdullah, M. A.; Batool, S.; Bawa, S.
Abstract : Background: Rheumatology has entered the era of biosimilar drugs. Compared with the original approved biological drug, a biosimilar has highly similar physiochemical characteristics and biological activity 1 . There is also equivalent efficacy and no clinically meaningful differences in safety and immunogenicity 1 . Substantial cost savings can be made by starting both biological-naive patients and switching patients receiving original biological DMARDs (bDMARDs) to biosimilar DMARDs (bsDMARDs) 2 . We present our experience of switching to biosimilars at Gartnavel General Hospital, Glasgow, UK. Objectives: To assess the adherence to bsDMARDs in patients switched from original bDMARDs and to identify factors affecting adherence Methods: We identified 69 patients on etanercept and 101 patients on adalimumab who were switched to bsDMARDs. We used patient clinical records and DA28 scores held in our database to assess the response to treatment and identify patients who were switched back to original bDMARD. We also identified the reason for switching back to bDMARDs and any safety concerns were also analysed. Results: Retention rate was 79.71% (55/69) in biosimilar etanercept and 90.10% (91/101) in biosimilar adalimumab group respectively. The overall failure rate was 20.29% (14/69) in biosimilar etanercept and 9.90% (10/101) in biosimilar adalimumab group. 15.94% (11/69) in biosimilar etanercept and 7.92% (8/101) in biosimilar adalimumab group were switched back to original bDMARD due to perceived disease flare. Control was regained in all these patients. Only 2 patients in each group (biosimilar etanercept – 2.9%, biosimilar adalimumab 1.98%) had clinically active disease requiring switch to bDMARD with different mechanism of action. 1 patient in biosimilar etanercept group had to stop biologic treatment due to cancer diagnosis. Conclusion: Our study showed overall adherence was good (around 80%) in both switch groups with biosimilar adalimumab doing better than biosimilar etanercept patients. All patients who switched back to bDMARD regained control. Nocebo responses 3, such as subjective increase of disease activity and pain-related adverse events were identified as the main factors having a negative impact on adherence to bsDMARDs. No new safety signals were identified. References: [1]Smolen JS, Goncalves J, Quinn M, et al. Era of biosimilars in rheumatology: reshaping the healthcare environment RMD Open 2019;5: e000900. doi: 10.1136/rmdopen-2019-000900 [2]National Institute for Health and Care Excellence Biosimilar medicines. 26 February 2016. Available at: https://www.nice.org.uk/advice/ktt15 [3]Planès S, Villier C, Mallaret M (2016) 'The nocebo effect of drugs', Pharmacology Research & Perspectives, 4(2), e00208. Acknowledgments: Rheumatology department, Gartnavel General Hospital, Glasgow, UK Disclosure of Interests: None declared